Manajemen Pendidikan Karakter Dalam Mewujudkan Generasi Muda Yang Berakhlakul Karimah di MI GUPPI At-Taqwa Ketosari, Bener, Purworejo - ., Eliyanto; Sulaimah, Siti; Wijayanti, Dian Inugrah (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2021)
This research is based on the importance of character education management in creating a young generation with good moral character. In connection with this, this research aims to determine the Management of Character Education in Creating a Young Generation with Characteristics at MI GUPPI AT-TAQWA Ketosari, Bener District, Purworejo Regency. This research is qualitative research. Data collection uses interviews, observation, and documentation, and data validity uses triangulation, and data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. This research produces five conclusions: (1) The instillation of values ​​and morality at MI GUPPI AT-TAQWA Ketosari Bener Purworejo is in accordance with the vision and mission of the madrasa, where the head of the madrasa is responsible for planning character education. The character values ​​instilled at MI Guppi Attaqwa Ketosari Bener Purworejo include: (a) religious character, (b) honesty character, (c) hard work character, (d) intelligent character, (e) caring character. (2) Modeling values ​​and morality at MI GUPPI AT-TAQWA Ketosari Bener Purworejo is carried out in various ways according to the style of each teacher, but the aim remains the same, namely to form good student character. Among the modeling of values ​​and morality implemented at MI GUPPI AT-TAQWA Ketosari is providing a good example to students, through a comprehensive approach, namely a way to overcome a problem. (3) Facilitating values ​​and morality carried out at MI GUPPI AT-TAQWA Ketosari Bener Purworejo includes activities to improve the relationship between educators and students, providing opportunities for students to express opinions, providing motivation to students. (4) Skills for developing moral values ​​and literacy at MI GUPPI AT-TAQWA Ketosari Bener Purworejo, namely: (a) critical thinking skills, (b) creative thinking skills, (c) clear communication skills, (d) listening skills. (5) Developing a values ​​education program at MI GUPPI AT-TAQWA Ketosari Bener Purworejo, namely through habituation activities carried out in daily, monthly and annual activities. Among these activities are congregational prayers, dhuha prayers, memorizing short surahs, memorizing Asmaul Husan, memorizing tahlil, tahlilan, tadarus, visiting graves, helping orphans, distributing basic necessities to the poor, and many other activities.